Mafhȗm ash-Shi’r ‘inda Qudâmah ibn Ja’far min Khilâl Kitâb “Naqd ash-Shi’r” - Hilda Dimyati Asmara (The Arabic Education Department Postgraduate Programs, UIN Sultan Maulana Hasanuddin Banten in Partnership with PPJKBA Indonesia, 2021)
It is not easy for the student in the present era to define the concept of poetry according to one of the ancients of criticism or creativity. This is because the simplest brick in the concept - which is the definition - has appeared in different forms for many of them; Each world has its own definition, according to their hurricane, culture, and perceptions; Where these definitions varied; Between focusing on meter and rhyme, and between highlighting quantity and quality, and between intent and intention, and between emphasizing systems and imagery. Through these various definitions and entry points, it seems to us how difficult this study lies. To derive the concept of poetry for a critic, creator or poet. Here we are in front of a flag of criticism, trying to define his concept of poetry, and to extract some criteria that make measured speech his poetry. This science is Qudamah bin Jaafar, and our work is based on his book “Naqd al-Sha’ir”, “which is considered the first famous scientific critical impact on Arabic literature, Through this research, the researcher tries to present some of the issues raised by Qudama bin Jaafar to define the concept of poetry in his book